Grounding Intelligibility, Safeguarding Mystery: A Neoclassical Reading of Ernan McMullin’s Legacy - Barzaghi, Amerigo (Religions, 2024)
This paper suggests a “neoclassical” reading of Ernan McMullin’s thought on science and theology. McMullin’s Augustinian convictions on God and the God–world relation coincide with those of some prominent scholars from two renowned schools of neo-scholastic philosophy of the twentieth century in Louvain and Milan. The school of Milan, thanks to the work of some disciples of its leading figure, Amato Masnovo, developed a neoclassical version of neo-scholasticism, articulating a fundamental theory of knowledge, as well as an essential, rigorous path to God. We recall the main tenets of a neoclassical path to God, and we interpret this path as a possible contribution to the science–theology dialogue, in line with McMullin’s Augustinism. A neoclassical approach to science and theology, with its rediscovery and reactualization of some ideas of classic philosophy in an interdisciplinary context, grounds the intelligibility of the universe and safeguards its mystery.